The determination of the total mass attenuation coefficients and the effective atomic numbers for concentrated colemanite and Emet colemanite clay - Icelli, Orhan; Yalcin, Zeynel; Okutan, Mustafa; Boncukcuoglu, Recep; Sen, Adem (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In this study, the attitude of some photon absorption energy related parameters such as coherent, Compton, photoelectric, pair-nuclear, pair-electronic, the total mass attenuation coefficients, effective atomic number, and electron density are investigated for two the mixtures, concentrated colemanite and Emet colemanite clay. In order to reach some desired conclusions, we calculated many of these parameters ranging from low energy (1 key) to high energy (100 MeV) by using WinXCom program. Radiation shielding of the materials are compared in terms of B(2)O(3) content. One of the most significant promise claimed by this study is that the excess or scarcity of B(2)O(3) content in any material may not be a defining parameter alone for environment, construction, radiation shielding, and neutron capture applications. As well as B(2)O(3) content, concentration values from quantitative and qualitative analysis of other compounds such as SiO(2), CaO, MgO. Fe(2)O(3), Al(2)O(3), PbO, K(2)O contained in a material, if existed, must be taken into account. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Mass attenuation coefficients; Effective cross-sections; Effective atomic number; Radiation shielding; Boron compounds; Clays; PHOTON INTERACTION; RADIATION TRANSMISSION; PORTLAND-CEMENT; BORIC-ACID; FLY-ASH; WASTE; ABSORPTION; BORON; BOROGYPSUM; PARAMETERS; Nuclear Science & Technology